Hubungan Usia dan Paritas dengan Kejadian Anemia pada Ibu Hamil di PMB Linda Elisabet Kecamatan Beji Kota Depok Provinsi Jawa Barat Tahun 2024 - Friza Novita Sari Situmorang; Evo Malini Silalahi; Damayanti Damayanti; Sonia Novita Sari; Rismalia Tarigan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
During pregnancy, anemia is a condition where the hemoglobin (Hb) level is <11 gr% in the first and third trimesters, while in the second trimester the mother's Hb level is <10.5 gr%. The aim of this research is to identify age and parity with the incidence of anemia in pregnant women in PMB Linda Elisabet, Beji District, Depok City, North Sumatra Province in 2024. This research used a Case Control design, the research time was April-June 2024, the population was 76 people, with a ratio of 1:1, the sampling technique used total sampling, using the Chi Square Test. The majority of respondents aged >20 years and >35 years did not experience anemia as many as 20 people (52.6%), respondents who had high parity status and experienced anemia were 18 people (47.4%). There is a significant relationship between the age and pair of pregnant women and the incidence of anemia in BPM Linda Elisabet, Beji District, Depok City, West Java Province with a p value <0.05 (0.001).